2022
DOI: 10.1111/nph.17939
|View full text |Cite
|
Sign up to set email alerts
|

The GA–DELLA–OsMS188 module controls male reproductive development in rice

Abstract: Summary Pollen protects male sperm and allows flowering plants to adapt to diverse terrestrial environments, thereby leading to the rapid expansion of plants into new regions. The process of anther/pollen development is coordinately regulated by internal and external factors including hormones. Currently, the molecular mechanisms underlying gibberellin (GA)‐mediated male reproductive development in plants remain unknown. We show here that rice DELLA/SLR1, which encodes the central negative regulator of GA si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 102 publications
0
16
0
Order By: Relevance
“…It is also reported that SLR1 interacts with an NUE and TN regulator, namely NGR5, to protect its degradation by the gibberellin receptor GID1 (Wu et al, 2020). Although the known function of SLR1 and its multiple reported mutants has been discussed (Ikeda et al, 2001;Asano et al, 2009;Hayashi-Tsugane et al, 2011;De Vleesschauwer et al, 2016;Jin et al, 2022), the natural variations or elite alleles have not been identified to date. We identified three missense SNPs of SLR1 between the two parents, which might be the causal mutations of the alleles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also reported that SLR1 interacts with an NUE and TN regulator, namely NGR5, to protect its degradation by the gibberellin receptor GID1 (Wu et al, 2020). Although the known function of SLR1 and its multiple reported mutants has been discussed (Ikeda et al, 2001;Asano et al, 2009;Hayashi-Tsugane et al, 2011;De Vleesschauwer et al, 2016;Jin et al, 2022), the natural variations or elite alleles have not been identified to date. We identified three missense SNPs of SLR1 between the two parents, which might be the causal mutations of the alleles.…”
Section: Discussionmentioning
confidence: 99%
“…A recent principal component (PC) analysis on eight typical traits related to the plant architecture of japonica rice varieties revealed that the first PCs indicated a trade-off between panicle sizes and numbers, and a GWAS with the PC scores identified the known genes NAL1 and OsGATA28, as well as a new gene OsSPY, the protein of which activates SLR1 (Yano et al, 2019). The possible candidate gene of qEPN-LN4/qEPN-HN3, namely SLR1, is related to gibberellin signaling and exerts pleiotropic effects, and additionally, SLR1 also works as a transcription factor of the GRAS-domain family and regulates many physiological processes as well as development (Ikeda et al, 2001;Fukao and Bailey-Serres, 2008;Huang et al, 2015;De Vleesschauwer et al, 2016;Lu et al, 2020;Mo et al, 2020;Jin et al, 2022). The molecular function of OsbZIP59 as a transcription factor may also have a pleiotropic effect on different traits by targeting different downstream genes.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous research also found that the miR156- SPL module may regulate male fertility in response to temperature changes, and OsSPL regulates the activity of APX, thereby regulating rice male fertility by controlling the programmed cell death (PCD) process in the tapetum. A recent study found that the GA negative regulator DELLA/SLR1 regulates premature PCD in the tapetum and affects the development process of the anthers ( Jin et al, 2022 ). Delayed degradation of the tapetum and abnormal development of the exine will lead to pollen abortion in some mutants, while the development of male gametophytes mainly occurs by integrating carbohydrate and fatty acid metabolism ( Zhang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In flowering plants, gibberellin-DELLA signalling promotes transition from the vegetative to the reproductive phase of the life cycle and coordination of male and female reproductive organ development (Plackett & Wilson, 2016). Arabidopsis and rice DELLAs are required for male reproductive development (Plackett et al, 2014;Jin et al, 2022) (Yasumura et al, 2007)). Physcomitrium tissue was cultured for phenotyping and spores germinated as described previously (Moody et al, 2012;Vesty et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…During restraint of vegetative growth, At DELLAs integrate light- and gibberellin signalling by interacting with the PHYTOCHROME INTERACTING FACTOR ( At PIF) transcription factors and preventing PIFs binding to the promoters of growth-promoting genes (de Lucas et al , 2008; Feng et al , 2008). In addition, during promotion of male reproductive development, the rice DELLA protein Os SLR1 interacts with the MYB protein Os MS188 (Jin et al , 2022).…”
Section: Introductionmentioning
confidence: 99%